Akt promotes Endocardial-Mesenchyme Transition - Meadows, Kafi N; Iyer, Seema; Stevens, Mark V; Wang, Duanning; Shechter, Sharon; Perruzzi, Carole; Camenisch, Todd D; Benjamin, Laura E (Vascular Cell, 2009)
Abstract Endothelial to mesenchyme transition (EndMT) can be observed during the formation of endocardial cushions from the endocardium, the endothelial lining of the atrioventricular canal (AVC), of the developing heart at embryonic day 9.5 (E9.5). Many regulators of the process have been identified; however, the mechanisms driving the initial commitment decision of endothelial cells to EndMT have been difficult to separate from processes required for mesenchymal proliferation and migration. We have several lines of evidence that suggest a central role for Akt signaling in committing endothelial cells to enter EndMT. Akt1 mRNA was restricted to the endocardium of endocardial cushions while they were forming. The PI3K/Akt signaling pathway is necessary for mesenchyme outgrowth, as sprouting was inhibited in AVC explant cultures treated with the PI3K inhibitor LY294002. Furthermore, endothelial marker, VE-cadherin, was downregulated and mesenchyme markers, N-cadherin and Snail, were induced in response to expression of a constitutively active form of Akt1 (myrAkt1) in endothelial cells. Finally, we isolated the function of Akt1 signaling in the commitment to the transition using a transgenic model where myrAkt1 was pulsed only in endocardial cells and turned off after EndMT initiation. In this way, we determined that increased Akt signaling in the endocardium drives EndMT and discounted its other functions in cushion mesenchymal cells.